2019
DOI: 10.2472/jsms.68.191
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation Behavior and New Classification of β-relaxation Region in Pd-based Metallic Glass

Abstract: We have focused on a rejuvenation behavior of recovery annealed Pd42.5Cu30Ni7.5P20 metallic glass. Specific heat measurement results revealed that only 33%, which is lower than that (44%) of a Zr50Cu40Al10 metallic glass, was recovered by annealing. This result indicates that the recovery of a Pd42.5Cu30Ni7.5P20 metallic glass is more difficult than the Zr-based alloy. The hardness measurement results obtained from the indentation test also supported this finding. The time dependence of the normalized storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…This suggests the relaxation state could be controlled solely through a conventional thermal process. We confirmed that rejuvenation can occur in fully relaxed Zr-Al-Ni-Cu and Pd-Cu-Ni-P disc metallic glasses, accompanied by an increase in relaxation enthalpy, a decrease in density, and mechanical softening by annealing at temperatures higher than T g followed by cooling at a rate of a few K s -1 [16,40]. These results demonstrate the occurrence of rejuvenation caused by the simple process of annealing and cooling.…”
Section: Introductionsupporting
confidence: 74%
“…This suggests the relaxation state could be controlled solely through a conventional thermal process. We confirmed that rejuvenation can occur in fully relaxed Zr-Al-Ni-Cu and Pd-Cu-Ni-P disc metallic glasses, accompanied by an increase in relaxation enthalpy, a decrease in density, and mechanical softening by annealing at temperatures higher than T g followed by cooling at a rate of a few K s -1 [16,40]. These results demonstrate the occurrence of rejuvenation caused by the simple process of annealing and cooling.…”
Section: Introductionsupporting
confidence: 74%